Filogeografia e limite específico do complexo Leptodactylus latrans de espécies (Amphibia, Anura, Leptodactylidae) na América do Sul - Magalhães, Felipe de Medeiros (2019)
The Leptodactylus latrans species group (Anura: Leptodactylidae) includes morphologically cryptic taxa widely distributed in South America (from Venezuela to northern Argentina, east of Andes), occurring along all Brazilian biomes and along an altitudinal gradient ranging from 0 to ~1500m above sea level. The delimitation of the species in this group is historically problematic due to the wide geographical distribution and the existence of morphologically cryptic species that do not exhibit discrete diagnostic morphological characters (for instance, L. latrans/chaquensis/macrosternum). Moreover, the lack of molecular and acoustic data also hampers a better understand concerning the species limit and diversity existing in this group. Therefore, the objective of this thesis is: 1 – to delimit in an integrative approach (using several sourcers of evidence) the specific limits of the Leptodactylus latrans complex species; 2 – investigate diversification scenarios for this group. To do so, I assambled an extensive database including genetic information (717 sequenced specimens and six molecular markers, two mitochondrial and four nuclear), morphometric (with 811 measured specimens) and acoustic (recordings for all species) covering the entire geographical distribution range of the L. latrans group. Among the main results, we propose a wide geographic distribution of L. macrosternum in South America, supported by the absence of phylogeographic structure (cohesive genetic lineage). In contrast, molecular, acoustic and morphological data corroborate the existence of four lineages with high genetic divergence and coherent geographic pattern (including the nominal L. latrans lineage). Therefore, I restrict the occurrence of L. latrans to the coastal Atlantic Forest of Brazil (from north of São Paulo to Bahia), also propose the revalidation of one species (L. luctator) and describe two new species for the complex. Finally, these results reinforce the importance of an integrative approach for taxonomic resolutions in a morphologically cryptic and widely distributed taxa, demonstrating that the knowledge on patterns of species diversity in the neotropical region is still depreciated.